RELATIONSHIPS BETWEEN HEAVY METALS AND IRON OXIDES, FULVIC ACIDS, PARTICLE SIZE FRACTIONS IN URBAN ROADSIDE SOILS - Wang X.; Qin Y. (My University, 2007)
Urban roadside soils are the “recipients” of large amounts of heavy metals from a variety of sources including vehicle emissions, coal burning waste and other activities. The behavior of heavy metals in urban roadside soils depends on the occurrence as well as the total amount. Accordingly, knowledge of the interactions between heavy metals and other constituents in the soil is required to judge their environmental impact. In this study, correlations of heavy metal concentrations (Pb, Zn, Cu, Ag, Se, Ni, Cr and Ba) to iron extracted using dithionite–citrate–bicarbonate (DCB) buffer (FeDCB), fulvic acids and particle size fractions were examined from the Xuzhou urban roadside soils. Heavy metals except for Cr and fulvic acids had a positive significant correlation with FeDCB, indicating these metals and fulvic acids are principally associated with the surfaces of iron oxides of the soils. Significant positive correlations were also found between the contents of fulvic acids and heavy metals, showing these heavy metals (especially for Cu, Ni and Cr) form stable complexes with fulvic acids. Such finding is of importance with regard to the increased mobilization of heavy metals, e.g., into freshwater ecosystems. Ag, Se and Cr are independent of particle size fractions because of their low concentrations of Ag and Se in the studied soils. Pb, Zn, Cu, Ba and Ag are mainly enriched in the finer soil particles (especially <16 μm).
Keywords: DITHIONITE-CITRATE-BICARBONATE BUFFER EXTRACTION; IRON OXIDES; FULVIC ACIDS; PARTICLE SIZE FRACTION; URBAN ROADSIDE SOILS; XUZHOU; CHINA